Strategies to Increase Postpartum Contraception in Palu City - Suarayasa, Ketut; Yane, Elli; Miranti, Miranti; Fitriana, Yuli (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Fertility is contributed to the high birth rate, mortality, and migration. One effort to control the birth rate is through the family planning program, using contraceptives by couples of childbearing age. The family planning program regulates the distance between mothers’ pregnancies, prevents early or late age pregnancies, has quality reproductive health, and reduces maternal mortality. AIM: This study aims to assess the effectiveness of the balanced family planning counseling strategy (BFP-CS) educational model on changes in postpartum contraception behavior in pregnant women. METHODS: The research used a quasi-experiment design with a non-randomized pre-test and post-test design, with a control group design. The study consisted of one intervention group (Talise Public Health) and one control group (Singgani Public Health), Palu city, with a purposive sampling technique of 43 respondents per group. Data were analyzed using univariate and bivariate. RESULTS: The results showed that there was a significant improvement in knowledge (p = 0.00), attitude (p = 0.00), intention (p = 0.00), and the use of postpartum contraceptives (p = 0.00) before and after treatment. A significant difference was revealed between intervention and control groups on knowledge (p = 0.036), attitude (p = 0.01), intention (p = 0.00), and the use of postpartum contraceptives (p = 0.00). CONCLUSIONS: Implementing the educational model of the BFP-CS could be an effective solution to improve knowledge, attitudes, intentions, and the use of postpartum contraceptives compared to the usual counseling method.